Estudio de las técnicas artesanales tradicionales de la parroquia y comunidad tigua, cantón Pujilí, provincia de Cotopaxi - Baño Lascano, Jessica Maribel (2016)
The present project of research denominated "STUDY OF TRADITIONAL CRAFT TECHNIQUES OF PARISH AND COMMUNITY TIGUA, CANTON PUJILI, PROVINCE OF COTOPAXI" is development in base to three objectives established the first was a diagnostic which information obtained in the aspect geographical, demographic, social, economic and cultural through interviews to the Autonomous Decentralized Government Parish Rural Zumbahua to know the current state of the sector, in the second objective is performed the Inventory of crafts techniques through files of the INPC (National Heritage Institute), the information was gathered through interviews to the craftsmen of the Parish Zumbahua and Tigua Community the same allowed to obtain information to register the data in the inventory, the third objective was the elaboration of the Guide craft techniques through the systematization of the data, which made reference them materials, processes and techniques of the activity craft since the research proposed rescue and spread them knowledge ancestral of the culture indigenous.